Causal relationship between immune cells and risk of heart failure: evidence from a Mendelian randomization study - Wenjing Cao; Zefu Yang; Liumei Mo; Zhenhao Liu; Jiawei Wang; Zhenhong Zhang; Kui Wang; Wei Pan (Frontiers in Cardiovascular Medicine)
BackgroundHeart failure (HF) is a clinical syndrome resulting from structural damage or dysfunction of the heart. Previous investigations have highlighted the critical involvement of immune cells in the progression of heart failure, with distinct roles attributed to different types of immune cells. The objective of the current research was to explore the potential connections between immune characteristics and the development of HF, as well as to ascertain the nature of the causality between these factors.MethodsTo assess the causal association of immunological profiles with HF based on publicly available genome-wide studies, we employed a two-sample Mendelian randomization technique, utilizing the inverse variance weighted (IVW) method as our primary analytical approach. In addition, we assessed heterogeneity and cross-sectional pleiotropy through sensitivity analyses.ResultsA two-sample Mendelian randomization (MR) analysis was conducted using IVW as the primary method. At a significance level of 0.001, we identified 40 immunophenotypes that have a significant causal relationship with HF. There is a significant causal relationship between these phenotypes and heart failure. These immunophenotypes, 8 of which were in B cells, 5 in cDC, 2 in T cell maturation stage, 2 in monocytes, 3 in myeloid cells, 7 in TBNK and 13 in Treg. Sensitivity analyses were conducted to validate the strength and reliability of the MR findings.ConclusionsOur study suggests that there appears to be a causal effect between multiple immune cells on heart failure. This discovery provides a new avenue for the development of therapeutic treatments for HF and a new target for drug development.